An Experimental Study on Phases of Vibrations Caused by Magnetostriction and Electromagnetic Force - Yifei Cai; Fares S. EL-Faouri; Akira Chiba; Souichiro Yoshizaki (IEEE Open Journal of Industry Applications)
Magnetostriction and electromagnetic force are the two electromagnetic sources of motor vibration. Understanding the phases of the vibrations caused by these two factors is crucial for determining whether they interact to amplify or mitigate total vibration. This study focuses on the experimental investigation of the phase behaviors of these two types of vibrations. A frequency-dependent phase delay between magnetostrictive strain and flux density is observed when measuring the magnetostriction curves of three core materials. However, similar phase delay cannot be confirmed between the magnetostrictive vibration and flux density in three stator cores. Instead, the magnetostrictive vibration is found to be in phase with the flux density even under high-frequency excitations. In addition, the vibration caused by electromagnetic force is measured in a switched reluctance motor, which also demonstrates an anti-phase relationship with the flux density. These experimental findings provide fundamental insights into magnetostrictive vibration, which will guide further research on motor vibration considering magnetostriction effect.